A quantitative model for trade pathway analysis of plant pest entry and transfer to a host in European Union territory1. (29th June 2017) - Holt, J.; Leach, A. W.; MacLeod, A.; Tomlinson, D.; Christodoulou, M.; Mumford, J. D.
Abstract : A quantitative pathway model, QPAFood, has been designed to support risk assessment for plant pest entry into European Union (EU) territory on a range of edible plant commodities via trade flows. The model calculates the distribution of an imported infested/infected commodity along a pathway into and within the EU from source countries, based on Eurostat data and other data/information. The model determines the implications of global trade pathways for the potential arrival of the infested commodity in the EU28 Member States. Within each Member State, the calculation proceeds by distributing the commodity according to uses, notably retail or processing, to the vulnerable area of commercial host crops determined in each NUTS2 region and then quantifies the consequent potential for pest–host contact which could lead to pest transfer. Annual and monthly estimates of contact risk are tabulated and visualized for Member States and NUTS2 regions. The model was developed originally for the European Food Safety Authority using four case studies of specific pest–commodity combinations. These pests had relatively limited host ranges and the model has now been extended in the context of the EC FP7 DROPSA project for the multiple commodity pathways associated with the highly polyphagous fruit pest Drosophila suzukii .